Disability in the Workplace A Caribbean Perspective - Stephenson, Jacqueline H.; Persadie, Natalie (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book critically examines equality, diversity, discrimination and inclusion in the English-speaking Caribbean, with specific emphasis on persons with disabilities (PWD). The text includes an evaluation of extant theoretical and empirical literature on PWD in employment, exploring the nature of their disabilities, the role of information technology and an analysis of the applicable laws and policies which prohibit discrimination against PWD in the Anglophone Caribbean. Though the enactment of legislation outlawing discrimination of PWD is not currently widespread in the Caribbean, some island states (namely Jamaica, Trinidad and Tobago, the Bahamas, Guyana, Antigua and Barbuda, and St. Lucia), have taken this positive step towards protecting this vulnerable group, while recognising the need to achieve inclusion of PWD within society, particularly in the areas of employment, education and accessing consumer products and services. For PWD and their allies, "nothing about us, without us" is an oft-cited refrain, highlighting the importance of being consulted when decisions, for example, in relation to access and accommodations at work, are being made. PWD are a heterogeneous group and, as such, the application of prevailing stigmas and stereotypes will invariably have an adverse effect on job seekers or employees with disabilities. In addition to literature-based analyses, the book also includes qualitative case studies, with the goal of providing benchmarks in organisational responses to employees with disabilities. Furthermore, the authors highlight lessons to be learned from other jurisdictions, in addressing inequalities, discrimination and exclusion within the organisational context for PWD. With its analysis of employment as well as socio-economic and legal issues, this interdisciplinary text will serve as a useful resource, in facilitating an understanding of organisational challenges faced by PWD, in contemporary Caribbean organisations and charting a path to effectively addressing them. Jacqueline H. Stephenson is Lecturer in the Department of Management Studies at the University of West Indies, Trinidad and Tobago. Natalie Persadie is Assistant Professor in the Mechanical Engineering, Manufacturing and Entrepreneurship Unit at the University of Trinidad and Tobago.
Chapter 1 - Introduction - Disability and discrimination -- Chapter 2 - The nature of disabilities in the Caribbean -- Chapter 3 - Education and persons with disabilities in the Caribbean: A Law and Policy Perspective -- Chapter 4 - Disability, information technology, assistive devices and employment in the Caribbean -- Chapter 5 - Mental health disabilities and work in the Caribbean region -- Chapter 6 - Neurodiversity in the Anglophone Caribbean -- Chapter 7 - Disability, Employment and Law: A Caribbean Outlook -- Chapter 8 - Discrimination against persons with disabilities: Lessons from other jurisdictions -- Chapter 9 - Experiences of disabled persons in employment in the Caribbean region -- Chapter 10 - Conclusion.
Keywords: Personnel management; Industrial organization; Management; Diversity in the workplace; Strategic planning; Leadership; Business ethics; Human Resource Management; Organization; Management; Diversity Management and Women in Business; Business Strategy and Leadership; Business Ethics